Heavy metal determination in atmospheric deposition and other fluxes in northern France agrosystems - Azimi, S.; Cambier, P.; Lecuyer, I.; Thevenot, D. (Water Air Soil Pollut., 2004)
The aim of this study is to assess the annual balance of the fluxes of Cd, Cu, Ni, Pb and Zn within different cropping systems, in an experimental site located near Versailles, France. Four fluxes through the cultivated horizon were considered to assess the annual heavy meta